Avaliação e manejo da oclusão trombótica de cateteres de longa permanência dos pacientes em hemodiálise - Amaral, Marcela Lara Mendes [UNESP] (2013)
Thrombosis of tunneled central venous catheters (CVC) in hemodialysis (HD) patients is common and it can lead to elimination of vascular sites. This study aimed to evaluate the incidence of thrombotic obstruction of CVC in HD patients and the efficacy of occlusion treatment with alteplase use, and identify factors associated with thrombotic occlusion. It was a prospective cohort study performed in two centers which evaluated the diagnosis and treatment of thrombotic occlusion of CVC in HD patients for 24 consecutive months. The catheter occlusion was defined as the difficulty to infuse or withdraw fluid from their paths. Alteplase dose was infused to fill the lumen of occluded catheter and remained for 50 minutes. Since there was no obstruction of the catheter, the procedure was repeated. Alteplase cryopreservation was performed (50mg dissolved in 50ml of sterile water and subsequently divided into individual portions and stored at -20 ° C). Statistical analysis: Initially descriptive analysis of the population was performed and the occurrence of catheter thrombotic occlusion was established as dependent variable. For categorical variables, the Chisquare Test was used and for continuous variables, t Test or Mann - Whitney test. Subsequently, multivariate analysis was performed using logistic regression model. Difference was considered when p < 0.05. Three hundred thirty nine CVC in 247 patients were evaluated and followed totaling 67,244 CVC/ day. The median age was 58 (47-66) years , predominantly male (54 %) , diabetic nephropathy as the main cause of chronic kidney disease ( 44 % ) , internal jugular vein as the main site of implantation (82 %) , dialysis duration before CVC implantation of 119 (41.5 to 585.5) days . Eight hundred fifteen occlusion episodes were diagnosed (12 episodes per 1000 CVCP - day), with primary success with alteplase in 596 episodes (77 %) and secondary in 81 cases (10 %). In 99 episodes (13%) success was not ...